Double-layer solar cell hole transport structure and preparation method thereof
By using the full thermal evaporate method to prepare a double-layer hole transport layer in perovskite solar cells, the problems of low filling factor and difficult to conformal coverage in the prior art are solved, and efficient hole transport and high filling factor are achieved, which are suitable for a variety of solar cell structures.
Patent Information
- Application Number
- CN202311272939.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The filling factor of the physical deposition hole transport layer of the existing perovskite solar cells is low, and the solution method is difficult to cover in conformal shape, especially unfriendly to substrate Si batteries with suede structure.
A double-layer hole transport layer is prepared by the full thermal evaporation method. By depositing two hole transport layers of different materials on the conductive substrate, the material is selected from specific P-type and N-type semiconductor materials to achieve rapid transfer and efficient extraction of holes.
It achieves high filling factor, improves the efficiency of solar cells, is suitable for perovskite single-junction, multi-junction stacked, crystalline silicon-perovskite stacked solar cells, and maintains the integrity of the suede pyramid structure, and is suitable for flexible devices.
Smart Images

Figure CN119730556A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a double-layer solar cell hole transport structure and a preparation method. Background Art
[0002] Perovskite solar cells have attracted much attention from researchers in the field of new energy in recent years. Currently, the record efficiency of single-junction perovskite solar cells has reached 25.7%. The key parameter open circuit voltage (V oc ) can reach above 1.2 V, indicating a significant suppression of non-radiative recombination. The current research focus is mainly on V oc The research on fill factor (FF) is less popular. A higher FF requires a significant reduction in recombination centers, a high shunt resistance R sh and low series resistance R s Minimizing the leakage current caused by carrier recombination in the bulk and interface can achieve higher R sh , R s It is determined by the conductive substrate, electrons, hole transport layer and interlayer contact. The conductivity and mobility of the transport layer are crucial to achieving a higher FF. Based on these factors, a high FF requires a uniform and dense perovskite active layer, a charge transport layer, and efficient charge transport and extraction. In particular, with the continuous breakthroughs in key technologies, a way to further improve battery efficiency is the construction of tandem cells. Solar cells composed of two semiconductor materials with different band gaps can broaden the light absorption range. In silicon-perovskite solar cells, perovskites have high conversion efficiency in green and blue light, and silicon cells have advantages in red and infrared light. At present, the highest certified photoelectric conversion efficiency of perovskite / silicon tandem solar cells has exceeded 31%, which has far exceeded that of single-junction cells. The hole transport layers commonly used in tandem cells are poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), nickel oxide (NiO x ), self-assembled phosphate molecules (2PACz, Me-4PACz, MeO-PACz), etc. However, for Si cells with a velvet structure, the solution method for preparing HTL is not very friendly to them, and often destroys their velvet structure and cannot achieve conformal coverage. In addition, for industrialization, it is of great significance to use physical sputtering methods such as thermal evaporation and magnetron sputtering to prepare the transport layer. The most commonly used conformal technology for preparing NiO is magnetron sputtering. x Due to the poor intrinsic conductivity, its photovoltaic parameters are generally relatively low, especially the fill factor is very backward, which is obviously unfavorable for the preparation of large-area batteries.
[0003] Therefore, there is an urgent need for a solar cell hole transport layer structure that can solve the problems of low filling factor of physically deposited hole transport layers in existing perovskite solar cells and difficulty in conformal coverage by solution methods. Summary of the invention
[0004] In view of the shortcomings of the prior art described above, the present invention proposes an inverted perovskite solar cell with an ultra-high filling factor and a double-layer hole transport layer prepared by full thermal evaporation. This hole transport structure is suitable for perovskite single-junction, multi-junction stacked, crystalline silicon-perovskite stacked (flat, velvet, rough surface) solar cells, photodetectors, LEDs and other optoelectronic devices. In addition, it is suitable for flexible devices of the above devices because it has the advantages of low-temperature preparation and conformal coverage.
[0005] To achieve the above-mentioned purpose and other related purposes, the present invention provides the following technical solutions: a double-layer solar cell hole transport structure, which at least includes a conductive substrate, a perovskite layer and a hole transport layer, and at least two hole transport layers of different materials are arranged between the conductive substrate and the perovskite layer, and the different materials have different LUMO and / or HOMO energy levels.
[0006] Furthermore, the double-layer solar cell transmission structure is sequentially an electrode, an electron transport layer, a passivation layer, a perovskite layer, a hole transport layer 2, a hole transport layer 1, a conductive substrate (metal substrate, transparent conductive glass, etc.) or a bottom cell substrate (planar and velvet crystalline silicon bottom cells + tunneling junctions, planar and velvet crystalline silicon bottom cells + transparent conductive oxides, perovskite bottom cells, etc.), and various flexible substrates.
[0007] Further, the hole transport layer 1 material is selected from N,N,N',N'-tetrakis([1,1'-biphenyl]-4-yl)[1,1':4',1"-terphenyl]-4,4"-diamine, 2,2',7,7'-tetrakis(di-p-tolylamino)spiro-9,9'-bifluorene, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene, 9,9'-(1,1-biphenyl-4,4'- Any one or more of the following: 1. the material of the hole transport layer 2 is selected from copper phthalocyanine, phthalocyanine, nickel phthalocyanine, lead phthalocyanine, cobalt phthalocyanine, zinc phthalocyanine, iron phthalocyanine, copper thiocyanate, copper iodide, and silver iodide.
[0008] Furthermore, the passivation layer material on the upper side of the perovskite is selected from any one or more of lithium fluoride, magnesium fluoride, sodium fluoride, calcium fluoride, potassium fluoride, rubidium fluoride, cesium fluoride, piperazine hydroiodide, phenylethylamine hydroiodide or octylamine hydroiodide.
[0009] Furthermore, the two hole transport layers are both deposited on the conductive substrate by thermal evaporation.
[0010] The present invention also provides a method for preparing the double-layer solar cell hole transport structure as described above, the specific steps are as follows:
[0011] 1) preparing a hole transport layer 1 and a hole transport layer 2 on a clean ITO substrate;
[0012] 2) depositing a perovskite layer on the layer obtained in step 1);
[0013] 3) depositing a passivation layer on the layer obtained in step 2);
[0014] 4) preparing an electron transport layer on the layer obtained in step 3);
[0015] 5) A back electrode is prepared on the layer obtained in step 4).
[0016] Furthermore, the hole transport layer 1 has a thickness of 5-15 nm, and the hole transport layer 2 has a thickness of 5-10 nm.
[0017] Furthermore, the hole transport layer 1 and the hole transport layer 2 are each independently prepared by a thermal evaporation method.
[0018] Furthermore, the two hole transport layers are deposited on the conductive substrate by thermal evaporation.
[0019] The present invention also provides a solar cell, comprising the double-layer solar cell hole transport structure as described above or a structure prepared by the preparation method as described above.
[0020] This solution can be applied to formal devices (NIP) and trans devices (PIN). The examples are trans devices (transparent conductive substrate / hole transport layer 1 / hole transport layer 2 / perovskite layer / passivation layer / electron transport layer / back electrode) and formal devices (transparent conductive substrate / electron transport layer / perovskite layer / passivation layer / hole transport layer 2 / hole transport layer 1 / back electrode).
[0021] Specifically, the hole transport layer structure of the solar cell is not only used for single-junction cells, but also can be used in crystalline silicon perovskite-stacked cells, perovskite-perovskite-stacked cells, perovskite-copper indium gallium selenide-stacked cells and other stacked cells, especially for suede crystalline silicon-perovskite stacked cells, which can ensure that the suede pyramid structure is not destroyed.
[0022] Specifically, for the solution method preparation of the hole transport layer, one or more p-type semiconductor materials such as poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), poly 3,4-ethylenedioxythiophene: polystyrene sulfonate (PEDOT:PSS), 4-butyl-N,N-diphenylaniline homopolymer (Ploy-TPD), self-assembled phosphoric acid molecules (2PACz, Me-4PACz, MeO-PACz) can be selected but are not limited to.
[0023] Due to the adoption of the above technology, the present invention has the following significant advantages compared with the prior art:
[0024] 1) The present invention realizes the rapid transfer of holes from the perovskite active layer to the transparent conductive substrate by setting two layers of P-type materials with different LUMO and HOMO as hole transport layers. This material and structure greatly promotes the extraction of holes and reduces the transition barrier, preventing the transition of electrons at this interface, inhibiting interface recombination, and making the device have excellent open circuit voltage and fill factor, thereby improving battery efficiency;
[0025] 2) The present invention adopts thermal evaporation to prepare two layers of hole transport layers, which can be prepared in large quantities. This structure is suitable for perovskite single junction, multi-junction stacking, crystalline silicon-perovskite stacking (flat, velvet, rough surface) solar cells, photodetectors, LEDs and other optoelectronic devices. In addition, flexible devices suitable for the above devices have the advantages of low-temperature preparation and conformal coverage; a two-layer hole transport layer structure is designed by full thermal evaporation, which can solve the problem of solution method preparation of hole transport layer to the velvet pyramid structure of silicon cell surface in velvet crystalline silicon-perovskite stacking cell, and solve the problem that the open circuit voltage and filling factor of perovskite solar cells with physical vapor deposition hole transport layer are low, and the traditional solution method is difficult to conform and uniformly cover the crystalline silicon velvet pyramid. The extremely high filling factor is conducive to the application of large-area component solar cells, the process cost is low, and it is easy to achieve industrialization.
[0026] 3) The hole transport layer material used in the present invention has the remarkable characteristics of good thermal stability and air stability, which can ensure the long-term storage stability, thermal stability and operating stability of the battery, and is conducive to the long-term stable operation of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of a single-junction pin structure cell having a double-layer hole transport layer solar cell of the present invention;
[0028] Figure 2 A schematic diagram of a crystalline silicon-perovskite tandem cell having a double-layer hole transport layer solar cell of the present invention;
[0029] Figure 3 This is a scanning electron microscope image of Example 1 of the present invention;
[0030] Figure 4 The current density-voltage curves of single-junction pin cells of Example 1 and Comparative Examples 1, 2, and 3 of the present invention;
[0031] Figure 5 This is the current density-voltage curve of the single-junction pin battery in Example 2 of the present invention;
[0032] Figure 6 This is a cross-sectional morphology diagram of the crystalline silicon-perovskite tandem cell of Example 3 of the present invention;
[0033] Figure 7 This is the current density-voltage curve of the crystalline silicon-perovskite tandem battery of Example 3 of the present invention;
[0034] Figure 8 This is a morphology picture of the stacked battery prepared by the full thermal evaporation method HTL1+HTL2 in Example 3 of the present invention;
[0035] Fig. 9 This is a morphology picture of the stacked battery prepared by spin coating solution PTAA in control example 4 of the present invention. DETAILED DESCRIPTION
[0036] In order to better understand the present invention, the present invention is further described in detail below in conjunction with specific implementation cases. These embodiments are used to illustrate the main reactions and basic features of the present invention, and are not limited to the following implementation cases. The implementation conditions adopted in the implementation cases can be further adjusted according to specific requirements, and the unspecified implementation conditions are usually the conditions in conventional experiments.
[0037] In the present invention, the second hole transport layer (hole transport layer 2) has excellent thermal stability, high carrier mobility, and fast hole transport rate. The first hole transport layer (hole transport layer 1) mainly acts as a buffer layer. This type of material itself is also a commonly used hole transport material. Their LUMO energy level is shallower than that of the hole transport layer 2, which can prevent the transfer of electrons to this side, while the position of the HOMO energy level is just suitable for the transfer of holes to the transparent conductive bottom, thereby reducing the potential barrier and achieving a higher level of filling factor.
[0038] In the present invention, the P-type transport layer material has been mentioned in the above technical content, and the N-type electron transport layer can be made of fullerene (C 60 , C 70 ) and their derivatives (PCBM, ICBA, etc.), but not limited to the transmission layer materials listed above.
[0039] Passivation layer materials include but are not limited to inorganic materials such as lithium fluoride (LiF), magnesium fluoride (MgF2), sodium fluoride (NaF), calcium fluoride (CaF2), potassium fluoride (KF), rubidium fluoride (RbF), cesium fluoride (CsF) and organic materials such as piperazine hydroiodide (PI), phenylethylamine hydroiodide (PEAI), octylamine hydroiodide (OAI), but are not limited to the above materials.
[0040] The above solution is further described below in conjunction with specific embodiments.
[0041] Example 1
[0042] This embodiment 1 adopts Figure 1 The structure shown in the figure is used to prepare a single-junction pin structure perovskite solar cell with a double-layer hole transport layer. The specific preparation process is as follows:
[0043] 1) The ITO substrate was cleaned with deionized water, acetone, and isopropanol in sequence, dried with nitrogen, and then cleaned with UV-ozone for 20 minutes. Then, it was transferred to a thermal evaporation chamber and deposited to prepare a hole transport layer 1 of about 15 nm. The deposition rate of the first 5 nm was The rate after 5nm is
[0044] 2) Thermally evaporate a hole transport layer 2 of about 5 nm on the prepared hole transport layer 1 at a deposition rate of
[0045] 3) Spin-coat a layer of Cs with a band gap of 1.65 eV, a concentration of 1.5 M, and a composition of Cs on the prepared double-layer hole transport layer. 0.25 FA 0.75 PbI 2.55 Br 0.45 The perovskite solution was heated at a speed of 5000 rpm / s for 35 seconds. Ethyl acetate (EA) was added as an anti-solvent in the last 15 seconds, followed by annealing at 100 °C for 30 minutes. The thickness was about 500 nm.
[0046] 4) Spin coating a passivation layer solution on the prepared perovskite at a rotation speed of 5000 rpm / s, followed by annealing at 100° C. for 5 minutes;
[0047] 5) Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as an electron transport layer with a thickness of about 25 nm;
[0048] 6) Using thermal evaporation at C 60 A layer of bathocuproin (BCP) is deposited as a buffer layer with a thickness of about 5 nm;
[0049] 7) A layer of Ag as an electrode was deposited on the BCP using thermal evaporation with a thickness of about 100 nm.
[0050] The device results of Example 1 and the results of Comparative Examples 1 and 2 are as follows: Figure 4 As shown, under the condition of one sun illumination, the open circuit voltage and fill factor of Example 1 are significantly higher than those of the control group.
[0051] Example 2
[0052] This embodiment 2 adopts Figure 1 The structure shown in the figure is used to prepare a single-junction pin structure perovskite solar cell with a double-layer hole transport layer. The specific preparation process is as follows:
[0053] 1) The ITO substrate was cleaned with deionized water, acetone, and isopropanol in sequence, dried with nitrogen, and then cleaned with UV-ozone for 20 minutes. Then, it was transferred to a thermal evaporation chamber and deposited to prepare a hole transport layer 1 of about 15 nm. The deposition rate of the first 5 nm was The rate after 5nm is
[0054] 2) Thermally evaporate a hole transport layer 2 of about 5 nm on the prepared hole transport layer 1 at a deposition rate of
[0055] 3) Spin-coat a layer of Cs with a band gap of 1.54 eV, a concentration of 1.4 M, and a composition of Cs on the prepared double-layer hole transport layer. 0.01 (FA 0.97 MA 0.03 )Pb(I 0.97 Br 0.03 )3 perovskite solution, with a rotation speed of 5000 rpm / s for 35 s, ethyl acetate (EA) was added as an anti-solvent in the last 15 s, and then annealed at 100 °C for 30 min, with a thickness of about 500 nm;
[0056] 4) Spin coating a passivation layer solution on the prepared perovskite at a rotation speed of 5000 rpm / s, followed by annealing at 100° C. for 5 minutes;
[0057] 5) Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as an electron transport layer with a thickness of about 25 nm;
[0058] 6) Using thermal evaporation at C 60 A layer of bathocuproin (BCP) is deposited as a buffer layer with a thickness of about 5 nm;
[0059] 7) A layer of Ag as an electrode was deposited on the BCP using thermal evaporation with a thickness of about 100 nm.
[0060] Example 2 and Example 1 used perovskites with different band gaps as the active layer, and both obtained good photovoltaic parameters, indicating good universality.
[0061] Example 3
[0062] This embodiment 3 adopts Figure 2 The structure shown in the figure is used to prepare a crystalline silicon / perovskite stacked solar cell with a double hole transport layer. The specific preparation process is as follows:
[0063] 1) The suede silicon cell was cleaned several times with isopropanol, dried with nitrogen, and then cleaned with UV-ozone for 20 minutes. Then, it was transferred to a thermal evaporation chamber and deposited to prepare a hole transport layer 1 of about 15 nm. The deposition rate of the first 5 nm was The rate after 5nm is
[0064] 2) Thermally evaporate a hole transport layer 2 of about 5 nm on the prepared hole transport layer 1 at a deposition rate of
[0065] 3) Spin-coat a layer of Cs with a band gap of 1.65 eV, a concentration of 1.5 M, and a composition of Cs on the prepared double-layer hole transport layer. 0.25 FA 0.75 PbI 2.55 Br 0.45 The perovskite solution was run at 1000 rpm / s for 10 s, then at 5000 rpm / s for 35 s. Ethyl acetate (EA) was added as an anti-solvent in the last 15 s, and then annealed at 100 °C for 30 min. The thickness was about 1 μm.
[0066] 4) Spin coating a passivation layer solution on the prepared perovskite at a rotation speed of 5000 rpm / s, followed by annealing at 100° C. for 5 minutes;
[0067] 5) Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as an electron transport layer with a thickness of about 15 nm;
[0068] 6) Using atomic layer deposition in C 60 A layer of tin oxide (SnO x ) as a buffer layer with a thickness of about 5 nm;
[0069] 7) Using magnetron sputtering on SnO x A layer of indium zinc oxide (IZO) is deposited on top with a thickness of about 100 nm;
[0070] 8) A layer of Ag was deposited on the IZO using thermal evaporation as an electrode with a thickness of about 400 nm.
[0071] Example 3 is to apply the single junction cell structure of Example 1 to a silicon cell to construct a stacked cell. The interface SEM of the stacked cell is as follows: Figure 6 As shown, good photovoltaic parameters were obtained (such as Figure 7 This indicates that this hole transport structure is feasible as a connecting layer between two sub-cells in a tandem battery.
[0072] Comparative Example 1
[0073] The specific preparation process is as follows:
[0074] 1) The ITO substrate was cleaned with deionized water, acetone, and isopropanol in sequence, dried with nitrogen, and then UV-ozone cleaned for 20 minutes. Then, a layer of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) was prepared as a hole transport layer (solution method HTL1) by spin coating. PTAA was a 2 mg / ml chlorobenzene solution, the rotation speed was 4000 rpm / s, and annealed at 100°C for 10 minutes;
[0075] 2) Spin-coat a layer of Cs with a band gap of 1.65 eV, a concentration of 1.5 M, and a composition of Cs on the prepared double-layer hole transport layer. 0.25 FA 0.75 PbI 2.55 Br 0.45 The perovskite solution was heated at a speed of 5000 rpm / s for 35 seconds. Ethyl acetate (EA) was added as an anti-solvent in the last 15 seconds, followed by annealing at 100 °C for 30 minutes. The thickness was about 500 nm.
[0076] 3) Spin coating a passivation layer solution on the prepared perovskite at a rotation speed of 5000 rpm / s, followed by annealing at 100° C. for 5 minutes;
[0077] 4) Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as an electron transport layer with a thickness of about 25 nm;
[0078] 5) Using thermal evaporation at C 60 A layer of bathocuproin (BCP) is deposited as a buffer layer with a thickness of about 5 nm;
[0079] 6) A layer of Ag as an electrode was deposited on the BCP using thermal evaporation with a thickness of about 100 nm.
[0080] Comparative Example 2
[0081] The specific preparation process is as follows:
[0082] 1) The ITO substrate was cleaned with deionized water, acetone, and isopropanol in sequence, dried with nitrogen, and then cleaned with UV-ozone for 20 minutes. Then, it was transferred to a thermal evaporation chamber and a hole transport layer 2 with a thickness of about 5 nm was deposited at a deposition rate of
[0083] 2) Spin-coat a layer of Cs with a band gap of 1.65 eV, a concentration of 1.5 M, and a composition of Cs on the prepared double-layer hole transport layer. 0.25 FA 0.75 PbI 2.55 Br 0.45 The perovskite solution was heated at a speed of 5000 rpm / s for 35 seconds. Ethyl acetate (EA) was added as an anti-solvent in the last 15 seconds, followed by annealing at 100 °C for 30 minutes. The thickness was about 500 nm.
[0084] 3) Spin coating a passivation layer solution on the prepared perovskite at a rotation speed of 5000 rpm / s, followed by annealing at 100° C. for 5 minutes;
[0085] 4) Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as an electron transport layer with a thickness of about 25 nm;
[0086] 5) using thermal evaporation to deposit a layer of bathocuproin (BCP) as a buffer layer on C60 with a thickness of about 5 nm;
[0087] 6) A layer of Ag as an electrode was deposited on the BCP using thermal evaporation with a thickness of about 100 nm.
[0088] Comparative Example 3
[0089] The specific preparation process is as follows:
[0090] 1) The ITO substrate was cleaned with deionized water, acetone, and isopropanol in sequence, dried with nitrogen, and then UV-ozone cleaned for 20 minutes. Then, a layer of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) was prepared by spin coating as a hole transport layer (solution method HTL2). 2PACz was a 0.3 mg / ml ethanol solution, the rotation speed was 3000 rpm / s, and annealed at 100°C for 10 minutes;
[0091] 2) Spin-coat a layer of Cs with a band gap of 1.65 eV, a concentration of 1.5 M, and a composition of Cs on the prepared double-layer hole transport layer. 0.25 FA 0.75 PbI 2.55 Br 0.45 The perovskite solution was heated at a speed of 5000 rpm / s for 35 seconds. Ethyl acetate (EA) was added as an anti-solvent in the last 15 seconds, followed by annealing at 100 °C for 30 minutes. The thickness was about 500 nm.
[0092] 3) Spin coating a passivation layer solution on the prepared perovskite at a rotation speed of 5000 rpm / s, followed by annealing at 100° C. for 5 minutes;
[0093] 4) Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as an electron transport layer with a thickness of about 25 nm;
[0094] 5) Using thermal evaporation at C 60 A layer of bathocuproin (BCP) is deposited as a buffer layer with a thickness of about 5 nm;
[0095] 6) A layer of Ag as an electrode was deposited on the BCP using thermal evaporation with a thickness of about 100 nm.
[0096] Comparative Example 4
[0097] In this comparative example 4, a spin coating solution method is used to prepare a crystalline silicon / perovskite stacked solar cell with PTAA as a hole transport layer. The specific preparation process is as follows:
[0098] 1) The suede silicon cell was cleaned several times with isopropanol, dried with nitrogen, and then cleaned with UV-ozone for 20 minutes. Then, a layer of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) was prepared as a hole transport layer by spin coating. PTAA was a 2 mg / ml chlorobenzene solution, the spin speed was 4000 rpm / s, and annealed at 100°C for 10 minutes.
[0099] 2) Spin-coat a layer of Cs with a band gap of 1.65 eV, a concentration of 1.5 M, and a composition of Cs on the prepared double-layer hole transport layer. 0.25 FA 0.75 PbI 2.55 Br 0.45 The perovskite solution was run at 1000 rpm / s for 10 s, then at 5000 rpm / s for 35 s. Ethyl acetate (EA) was added as an anti-solvent in the last 15 s, and then annealed at 100 °C for 30 min. The thickness was about 1 μm.
[0100] 3) Spin coating a passivation layer solution on the prepared perovskite at a rotation speed of 5000 rpm / s, followed by annealing at 100° C. for 5 minutes;
[0101] 4) Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as an electron transport layer with a thickness of about 15 nm;
[0102] 5) Using atomic layer deposition in C 60 A layer of tin oxide (SnO x ) as a buffer layer with a thickness of about 5 nm;
[0103] 6) Using magnetron sputtering on SnO x A layer of indium zinc oxide (IZO) is deposited on top with a thickness of about 100 nm;
[0104] 7) A layer of Ag was deposited on the IZO using thermal evaporation as an electrode with a thickness of about 400 nm.
[0105] Comparative Example 4 applies the single-junction cell structure of Comparative Example 1 to a silicon cell to construct a stacked cell.
[0106] Example 4
[0107] By comparing Example 1 with Comparative Example 2 (such as Figure 4 As shown in the figure, it shows that the open circuit voltage of the double-layer hole transport layer structure is significantly improved compared with the single-layer structure, indicating that the interface recombination is suppressed.
[0108] Example 5
[0109] Example 3 and Comparative Example 4 are respectively suede crystalline silicon / perovskite laminated solar cells prepared by two different processes. Figure 8 As shown) and Comparative Example 4 (as Fig. 9 From the morphology of the graphite film (shown in the figure), it can be seen that for the stacked battery obtained by preparing two layers of hole transport layers by full thermal evaporation method, the perovskite film can uniformly and conformally cover the velvet pyramid. However, for the stacked solar cell obtained by spin coating PTAA by traditional solution method, the perovskite film cannot uniformly and conformally cover, and the pyramid will contact the upper film layer through the perovskite film, causing battery failure.
[0110] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limitations of the present invention. The protection scope of the present invention should be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims, that is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A double-layer solar cell hole transport structure, which comprises at least a conductive substrate, a perovskite layer and a hole transport layer, characterized in that: At least two hole transport layers made of different materials are arranged between the conductive substrate and the perovskite layer, and the different materials have different LUMO and / or HOMO energy levels.
2. The double-layer solar cell hole transport structure according to claim 1, characterized in that: The hole transport structure of the double-layer solar cell is sequentially an electrode, an electron transport layer, a passivation layer, a perovskite layer, a hole transport layer 2, a hole transport layer 1, a conductive substrate (metal substrate, transparent conductive glass, etc.) or a bottom cell substrate (planar and velvet crystalline silicon bottom cells + tunneling junctions, planar and velvet crystalline silicon bottom cells + transparent conductive oxides, perovskite bottom cells, etc.), and various flexible substrates.
3. The double-layer solar cell hole transport structure according to claim 1, characterized in that: The hole transport layer 1 material is selected from N,N,N',N'-tetrakis([1,1'-biphenyl]-4-yl)[1,1':4',1"-terphenyl]-4,4"-diamine, 2,2',7,7'-tetrakis(di-p-tolylamino)spiro-9,9'-bifluorene, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene, 9,9'-(1,1-biphenyl-4,4'-diyl) Any one or more of bis(N3,N3,N6,N6-tetrakis(4-methoxyphenyl)-9H-carbazole-3,6-diamine), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, tetracene, pentacene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine; the hole transport layer 2 material is selected from any one or more of copper phthalocyanine, phthalocyanine, nickel phthalocyanine, lead phthalocyanine, cobalt phthalocyanine, zinc phthalocyanine, iron phthalocyanine, copper thiocyanate, copper iodide, and silver iodide.
4. The double-layer solar cell hole transport structure according to claim 1, characterized in that: The passivation layer material on the upper side of the perovskite is selected from any one or more of lithium fluoride, magnesium fluoride, sodium fluoride, calcium fluoride, potassium fluoride, rubidium fluoride, cesium fluoride, piperazine hydroiodide, phenylethylamine hydroiodide or octylamine hydroiodide.
5. The double-layer solar cell hole transport structure according to claim 1, characterized in that: The two hole transport layers are both deposited on the conductive substrate by thermal evaporation.
6. The method for preparing a double-layer solar cell hole transport structure according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: 1) preparing a hole transport layer 1 and a hole transport layer 2 on a clean ITO substrate; 2) depositing a perovskite layer on the layer obtained in step 1); 3) depositing a passivation layer on the layer obtained in step 2); 4) preparing an electron transport layer on the layer obtained in step 3); 5) A back electrode is prepared on the layer obtained in step 4).
7. The preparation method according to claim 6, characterized in that: The thickness of the hole transport layer 1 is 5-15 nm, and the thickness of the hole transport layer 2 is 5-10 nm.
8. The preparation method according to claim 6, characterized in that: The hole transport layer 1 and the hole transport layer 2 are each independently prepared by a thermal evaporation method.
9. The preparation method according to claim 6, characterized in that: The two hole transport layers are both deposited on the conductive substrate by thermal evaporation.
10. A solar cell, characterized in that: It comprises a double-layer solar cell hole transport structure as described in any one of claims 1 to 5 or a structure prepared by the preparation method as described in any one of claims 6 to 9.
Citation Information
Patent Citations
A perovskite solar cell based on mesoporous inorganic hole transport material and a preparation method thereof
CN109103331A
Perovskite solar cell based on double-layer composite hole transport layer and preparation method
CN110246970A
Perovskite solar cell with double electron transport layers and double hole transport layers and preparation method of perovskite solar cell
CN110350092A
Double-hole transport layer perovskite solar cell and preparation method thereof
CN111403604A
Trans-perovskite solar cell with double hole transport layers and preparation method of trans-perovskite solar cell
CN114141948A
Cited By
Perovskite battery and preparation method thereof
CN120417630A
Perovskite / crystalline silicon laminated solar cell and packaging method and application thereof
CN121152480A